Single‐cell transcriptomics provides insights into the origin and microenvironment of human oesophageal high‐grade intraepithelial neoplasia. Issue 5 (24th May 2022) - Liao, Guobin; Dai, Nan; Xiong, Tiantian; Wang, Liang; Diao, Xinwei; Xu, Zhizhen; Ni, Yuanli; Chen, Dingrong; Jiang, Airui; Lin, Hui; Dai, Shuangshuang; Bai, Jianying
Abstract: Background: High‐grade intraepithelial neoplasia (HIN) is the precursor of oesophageal squamous cell carcinoma. The molecular and functional properties of HIN are determined by intrinsic origin cells and the extrinsic microenvironment. Yet, these factors are poorly understood. Methods: We performed single‐cell RNA sequencing of cells from HINs and adjacent tissues from the human oesophagus. We analysed the heterogeneity of basal layer cells and confirmed it using immunostaining. Aneuploid cells in HIN were studied using primary cell culture combined with karyotype analysis. We reconstructed the lineage relationship between tumour and normal populations based on transcriptome similarity. Integration analysis was applied to our epithelial data and published invasive cancer data, and results were confirmed by immunostaining and 3D organoid functional experiments. We also analysed the tumour microenvironment of HIN. Results: The basal layer contained two cell populations: KRT15 high STMN1 low and KRT15 high STMN1 high cells, which were located mainly in the interpapillary and papillary zones, respectively. The KRT15 high STMN1 low population more closely resembled stem cells and transcriptome similarity revealed that HIN probably originated from these slow‐cycling KRT15 high STMN1 low cells. 3D Organoid experiments and RNA‐sequencing showed that basal‐cell features and the differentiation ability of the normal epithelium were largely retained in HIN, but may change dramatically in tumour invasion stage. Moreover, the tumour microenvironment of HIN was characterised by both inflammation and immunosuppression. Conclusions: Our study provides a comprehensive single‐cell transcriptome landscape of human oesophageal HIN. Our findings on the origin cells and unique microenvironment of HIN will allow for the development of strategies to block tumour progression and even prevent cancer initiation. Abstract : A comprehensive single‐cell transcriptome landscape of human oesophageal high‐grade neoplasia. Basal layer cells are heterogeneous by transcriptome and location: KRT15 high STMN1 low and KRT15 high STMN1 high cells, which are located mainly at interpapillary zone and papillary zone, respectively. HIN probably originated from slow‐cycling KRT15 high STMN1 low cells. HIN is slightly biased in the transcriptome, which may change dramatically in tumour invasion stage.